Dual-Pathway Antithrombotic Therapy in Patients With Atrial Fibrillation After Percutaneous Coronary Intervention in Stable Coronary Artery Disease: A Single-Center, Single-Operator, Retrospective Cohort Study - Heger, Lukas Andreas; Danzer, Martin; Bode, Christoph; Hortmann, Marcus; Duerschmied, Daniel; Olivier, Christoph B.; Moser, Martin (Frontiers in Medicine, 2020)
Background: There is limited data evaluating the prescription practices for antithrombotic therapy in patients with atrial fibrillation (AF) following elective percutaneous coronary intervention (PCI). Objective: This single-centre, single-operator, retrospective cohort study aimed to evaluate trends of antithrombotic treatment strategies in patients with AF undergoing elective PCI. Methods: Patients with AF who electively underwent PCI performed by a single interventionalist between April 2013 and May 2018 were identified. The primary outcome was the antithrombotic therapy at discharge assessed by chart review: triple (TAT; triple antithrombotic therapy) or dual (DAT; dual antithrombotic therapy) antithrombotic therapy and vitamin K antagonist (VKA) or non-vitamin k antagonist oral anticoagulant (NOAC), respectively. Secondary outcomes were rehospitalisation, death, bleeding requiring medical attention and stroke and were assessed via questionnaires and telephone contact at 3 months, 1 year and 3 years after discharge. Results: Of 6,135 screened patient visits, 259 met the inclusion criteria. Among these, 133 (51%) patients received NOAC- and 126 (49%) VKA-therapy. Compared with patients on NOAC therapy, patients treated with VKA had higher bleeding risk (mean HAS-BLED -Score; 2.3 vs. 2.0; p=0.02) and more co-morbidities (estimated glomerular filtration rate < 30ml/min, 11% vs. 4%; p=0.04; diabetes mellitus, 33% vs. 20%; p=0.03; history of previous PCI, 37% vs. 21%; p=0.006). TAT was prescribed more frequently if the prescription included VKA compared with NOAC (61% vs. 42%; p=0.002). Prescription of TAT and VKA decreased throughout the observed period (2013:100% vs. 2018: 6%; p<0.001 and 2013: 91% vs. 2018: 28%; p<0.001). The median follow up was 401 (IQR 171-1104) days post PCI with no significant differences in secondary outcomes between patients treated with NOAC compared with VKA. Conclusion: These observational data from a single centre registry show a paradigm chance in antithrombotic therapy of AF patients over the last 6 years, with a decrease of TAT- and VKA- prescription in favour of DAT with NOAC. Whether these observations are consistent with national or global trends should to be evaluated in further studies.